IMF Staff papers : Volume 24 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1977)
This chapter focuses on the impact of monetary and fiscal policy under the flexible exchange rates and alternative expectations structures. Several economists have argued that, to understand recent exchange rate movements, one must examine the process by which exchange rate expectations are formulated. In order to describe the influence of exchange rate expectations on the adjustment process, this paper examines a small, open economy's response to either an increase in the money supply or a higher level of debt-financed government spending under the assumption that exchange rate expectations are either rational, semi-rational, or adaptive. It is argued that the economy's response to an increase in the money supply is much more sensitive to the expectations structure than is its response to an increase in government spending. The analysis also shows that, following an increase in the money supply, the exchange rate will overshoot its long term value regardless of the type of expectations structure that exists. The domestic interest rate will be the variable most strongly influenced by the way the private sector formulates its expectations.